A new member of the greater double-collared sunbird complex (Passeriformes: Nectariniidae) from the Eastern Arc Mountains of Africa - Bowie, Rauri C. K.; Fjeldså, Jon; Kiure, Jacob; Kristensen, Jan Bolding (Zootaxa, 2016)
We document the discovery of the first population of greater double-collared sunbird (Cinnyris afer complex) from the Eastern Arc Mountains of Tanzania. We assessed phylogenetic relationships and taxonomic rank based on mtDNA sequence data, nine microsatellite loci and morphology. This new taxon, locally distributed in the Rubeho and Udzungwa Highlands, has close affinities (< 1% uncorrected sequence divergence) with C. whytei (split here from C. ludovicensis) of the Nyika Plateau in Malawi, but differs in having longer tarsi and in subtle plumage details. Although the birds from Nyika and Udzungwa-Rubeho are reciprocally monophyletic for mitochondrial DNA, coalescent analyses of the microsatellite data and the total molecular dataset could not reject the possibility of continued gene flow between the two populations. Thus, although we favour the phylogenetic species concept, we adopt a cautious approach and formally describe the Rubeho and Udzungwa greater double-collared sunbird population as a subspecies of Cinnyris whytei. This new sunbird taxon has been recorded only above 1700 m in scrub on the forest/grassland ecotone in a very restricted area in the Rubeho and Udzungwa Highlands of Tanzania. The effects of human settlement and agriculture threaten this taxon.